Openmp and MPI Architectures for Simulating 1D Water Oscillation on Parabolic Domain - H. Gunawan, P.; Juliati, S.; R. Pahlevi, M.; Adytia, D. (International Journal of Engineering and Technology, 2019)
This paper enlightens the simulation of 1D water oscillation on parabolic domain using shallow water equations on multicore processing. Those equation is approached by using finite volume method staggered grid scheme. This scheme is known as a robust scheme for approximating the shallow water equations. Moreover, the scheme is also straightforward to transform into numerical codes.Â In this paper, the parallel architectures multicore processing OpenMP and MPI are used. The results are shown the CPU time of OpenMP and MPI are better than the serial programming when the number of grids is given more than 200 points. Moreover, the speedup of OpenMP is shown 3 times better than MPI with N_xÂ = 6400 points for both 4 and 8 processors. The maximum of efficiency in the simulation can be achieved around 75% withÂ N_xÂ = 6400 points by 4 cores using OpenMP. However, by 8 cores of processors using OpenMP, the maximum of efficiency is obtained around 60%.Â